2016
DOI: 10.1002/cam4.868
|View full text |Cite
|
Sign up to set email alerts
|

A cross‐sectional study comparing a blood test for methylated BCAT1 and IKZF1 tumor‐derived DNA with CEA for detection of recurrent colorectal cancer

Abstract: Recurrence will develop in 30–50% of colorectal cancer (CRC) cases despite apparent clearance following treatment. Carcinoembryonic antigen (CEA) is the only guideline‐recommended blood test for monitoring cases for recurrence, but its sensitivity and specificity are suboptimal. This observational study compared a novel 2‐gene (methylated BCAT1 and IKZF1 DNA) blood test with CEA for detection of recurrent CRC. We conducted a paired comparison of the BCAT1/IKZF1 test with CEA (cut‐off 5 ng/mL) in blood from pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
87
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 38 publications
(49 reference statements)
5
87
0
1
Order By: Relevance
“…Venous blood was collected (2 × 9‐mL K3‐EDTA vacutainers), prepared, and stored as previously described . All procedures were performed by hospital‐accredited specialists and met site‐specific standards.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Venous blood was collected (2 × 9‐mL K3‐EDTA vacutainers), prepared, and stored as previously described . All procedures were performed by hospital‐accredited specialists and met site‐specific standards.…”
Section: Methodsmentioning
confidence: 99%
“…One such ctDNA test is COLVERA, which detects hypermethylated regions within branched‐chain amino acid transaminase 1 ( BCAT1 ) and Ikaros family zinc‐finger 1 protein ( IKZF1 ) . Furthermore, an initial evaluation of these biomarkers when they were assessed in a qualitative manner showed that this methylated ctDNA test could be up to twice as sensitive for detecting recurrent CRC in comparison with CEA …”
Section: Introductionmentioning
confidence: 99%
“…[61][62][63][64][65][66][67][68][69] For example, an approach using a BCAT1 and IKZF1 methylation assay identified approximately 70% of CRC. [75][76][77] Detection of tumor recurrence, minimal residual disease, and prognosis value Surgery alone cures a large fraction of patients with localized CRC. However, there are currently no effective means to identify which patients have residual disease that will result in recurrence.…”
Section: Cancer Diagnosis and Screeningmentioning
confidence: 99%
“…As most patients with CRC are asymptomatic or have non-specific symptoms in the early stages, it is vital to find a safe, acceptable, sensitive, specific, and cost-effective test that detects the early stage of the disease [5]. …”
Section: Introductionmentioning
confidence: 99%
“…Blood-based markers in current use, such as carcinoembryonic antigen (CEA) and cancer antigen (CA) 19-9, are for surveillance and for monitoring response to treatment but have a low sensitivity and specificity ranging from 40 to 70% and 73 to 90%, respectively, making them unsuitable as screening or diagnostic markers [5, 10] A more recently proposed marker, which is commercially available, is methylated septin 9. This is a molecular-based blood test whose reported accuracy in the literature has been variable.…”
Section: Introductionmentioning
confidence: 99%